Black sails. The complete second season [videorecording (DVD)]. - Stephens, Toby, 1969-; Kennedy, Jessica Parker; Arnold, Luke; McGowan, Zach (Anchor Bay Entertainment, 2015)
The Walrus crew is stranded with an army of Spanish soldiers standing between them and their precious Urca gold. And with their crimes against their brethren no longer a secret, Flint and Silver must join forces in a desperate bid for survival. Meanwhile, Eleanor Guthrie struggles to maintain her grip on Nassau, as a new breed of pirate arrives in the form of Ned Low, a man for whom violence isn't just a tool, it's a pastime.